The contributions of Jean A. Laponce to political science - Safran, William (2018)
Jean A. Laponce contributed significantly to the study of political science, particularly in the fields of French and comparative politics, pluralism, the meaning of right and left, and the politics of ethnicity and language. His most influential writings focused on the politics of multilingual societies. He examined the place of language from three perspectives: the territorial imperative$1 (Ba bounded formal space providing safety and dominance for a single language; the problems of nonterritorially based linguistic minorities; and the rivalries and conflicts between languages in contact. Finally, he dealt with the survival of minority languages and the fate of languages globally. This review article evaluates Laponce$1 (Bs contributions to political science. - Reproduced.s
Keywords: Jean A. Laponce